Reaksi Pasar Modal terhadap Pengumuman Kebijakan Insentif Pajak Penjualan atas Barang Mewah - Suryani, Ayu Mirah; Noviari, Naniek (E-Jurnal Akuntansi; Vol 33 No 2 (2023), 2023)
The announcement of the Luxury Goods Value Added Tax Incentive policy (PPnBM) is an economic phenomenon that is used in studying capital market reactions. The research aims to empirically examine whether or not there is a significant abnormal return and trading volume activity before and after the announcement of the PPnBM Incentive policy. This type of research is an event study using a quantitative approach. The sample was selected by purposive sampling method, namely 13 automotive subsector companies listed on the IDX. This research uses one sample t-test as a tool in analyzing data. The results of the study show that there are no significant abnormal returns, but a significant trading volume activity indicates that this policy only changes the expectations of individual investors. It is hoped that investors will be able to make the right decisions to gain profits or reduce risks that may occur in the capital market. Keywords: Event Studies; Government Regulations; Abnormal Returns; Trading Volume Activity.